Factors influencing the adoption social media banking : a South African retail banking perspective - Twum-Ampofo, Yaw Ofosu (My University, 2018)
Social media banking has increasingly been adopted by western countries leading to the provision of banking products and services to a wider and younger base of customers. Social media banking in South Africa is still in its early stages and has thus far experienced a low rate of adoption by South African customers. This study aimed to identify the factors influencing the adoption of social media banking in South Africa. The study utilised the deductive research design methodology. Content of previous literature on technology adoption was discussed using the technology acceptance model (TAM), theory of reasoned action (TRA), theory of planned behaviour (TPB), innovation diffusion theory (IDT) and theory on trust, forming the basis in deriving the hypotheses for this study. Data was collected from a total of 233 respondents. 29 of these respondents did not complete the questionnaire, while one respondent did not give consent to partake in the questionnaire. These 30 respondents were excluded from the analysis. The remaining 203 usable responses were used to conduct the analysis. The findings of the study were analysed and are represented in frequency tables and graphs. A reliability analysis was conducted using Cronbach‟s alpha coefficient for internal consistency. This test aimed to measure how closely related each set of questions in the survey is to their construct. The Pearson product-moment correlation coefficient was then performed for each hypothesis to measure the strength of the linear relationship between each of the variables. An Analysis of variance (ANOVA) test was performed to determine whether there are statistically significant differences at a 95% confidence interval between the various age groups for each variable. The Tukey test was then conducted for each variable which were found to be statistically significant. The study identified relative advantage, complexity, compatibility, awareness, trialability, attitude, perceived usefulness, perceived ease of use, and trust to 2 have an influence on the probability of adoption of social media banking. The hypotheses were accepted at a 95% confidence interval. There was a generally negative sentiment towards social media banking with only 26.1% of respondents having a positive attitude towards it. However, the findings showed that males had a more positive attitude than females; with 30.7% of males being positive compared to 20.7% of females. Males were also more willing to adopt social media banking with 41.4% of males intending to adopt it compared to 33.7% of females. The study further showed that the younger group of respondents had a more positive attitude and were more trusting of social media banking. The recommendations flowing from the study are for South African banks to increase their awareness of their social media banking services and to educate customers regarding the security and confidentiality of the personal information aspects of social media banking. In addition to the recommendations, it is evident from the study that further research on this topic should encompass a broader view of the demographics of South Africa to get a better understanding of the demographics‟ probability of adoption of social media banking; and a consideration of the adoption of digital banking (including social media banking) in the SME segment needs to be conducted.
MBA
Keywords: Banks and banking, Mobile -- South Africa. Social media -- South Africa. Customer relations -- South Africa.